2006
DOI: 10.1590/s1413-86702006000500003
|View full text |Cite
|
Sign up to set email alerts
|

Serological markers of hepatitis A, B and C viruses in rural communities of the semiarid Brazilian Northeast

Abstract: In the village of Cavunge, located in a dry tropical, semiarid rural region of the state of Bahia, Brazil, a sentinel study on viral hepatitis is underway. We report on the first part of the study. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
1
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 21 publications
3
6
1
3
Order By: Relevance
“…Among the classical risk factors for HAV infection in developing countries investigated in this study, age, non-white skin color, crowding, educational level of the mother, and habit of swimming in rivers emerged as significant contributors to HAV seropositivity in Campos dos Goytacazes. Consistent with previous studies 10,27,29,31,32 , age was the most robust variable associated with the prevalence of anti-HAV antibodies. Logistic regression pointed to an increasing risk gradient as the age of the individuals increased.…”
Section: Discussionsupporting
confidence: 90%
“…Among the classical risk factors for HAV infection in developing countries investigated in this study, age, non-white skin color, crowding, educational level of the mother, and habit of swimming in rivers emerged as significant contributors to HAV seropositivity in Campos dos Goytacazes. Consistent with previous studies 10,27,29,31,32 , age was the most robust variable associated with the prevalence of anti-HAV antibodies. Logistic regression pointed to an increasing risk gradient as the age of the individuals increased.…”
Section: Discussionsupporting
confidence: 90%
“…The high prevalence was concentrated, as expected, in the northern region. However, two studies identified high endemicity outside the Amazon basin, in the semi-arid region of the State of Bahia and in African descendants from the Cerrado of the State of Mato Grosso do Sul (34) (36) . Five studies reported prevalence below 1%, and the other six assessed antiHBc positivity rather than HBsAg.…”
Section: Results From the Turn Of The Centurymentioning
confidence: 99%
“…However, there may be locations in the interior that require a better approach, as observed by Almeida et al (34) in the semi-arid region of Bahia during the 1990s (34) . At-risk groups were not addressed in this review because they are a signifi cant minority of the Brazilian population.…”
Section: Discussionmentioning
confidence: 96%
“…Comparando os dois grupos, verificou-se que no grupo 2 a prevalência de anti-VHA foi significativamente maior nos estratos de 1-4 anos (p = 0,02) e de 5-9 anos (p = 0,03) e que apresentou redução muito significativa entre [15][16][17][18][19] …”
Section: Resultsunclassified
“…No Brasil, estudos sorológicos têm demonstrado que a endemicidade da hepatite A está mudando na maioria das regiões, com taxas significativamente menores de anticorpo anti-VHA (anti-VHA) entre as crianças e os adolescentes [12][13][14][15] , especialmente de classe socioeconômica mais favorecida 12,14,15 . A região Norte 12 e algumas comunidades isoladas de outras regiões [16][17][18] , entretanto, continuam a apresentar prevalên-cia elevada, significativamente maior do que a taxa média de 65% estimada para o Brasil em estudo realizado entre 1996 e 1997 12 .…”
Section: Introductionunclassified